Optimized Wideband Beamforming for mm-wave Communication Systems with Intelligent Reflecting Surfaces - Hiba A. Alsawaf; Saad Ahmed Ayoob (Journal of Communications Software and Systems)
Millimeter wave-based intelligent reflecting surface communications represent a promising technology enabling 6G networks. However, taking advantage of the bandwidth of millimeter wave and the characteristics of IRS leads to the problem of beam splitting, which makes the precise steering of the resulting beams at all frequencies complicated, resulting in large losses in array gain. This paper investigated the effect of millimeter wave beam splitting IRS systems and developed an IRS structure based on the sub-surface of its elements. The basic idea is to introduce time delay (TD) and phase shift units into the IRS elements to perform common phase and pre-delay modulation instead of traditional phase shift. Therefore, a wideband phase shift design is proposed, and delay precoding compensates for the losses in array gain due to beam splitting. Large antennas are used in the base station, resulting in double beam splitting. An analysis of the effect of the double beam splitting on array gain was presented, along with some solutions aimed at improving the performance of phase conditioning and delay coding in the base station and IRS. The simulation results show that the proposed design, which is based on phase shift and TD, effectively overcomes the challenge of beam splitting. The proposed design demonstrated a gain improvement of 94.5% compared to the conventional approach. The results showed that the use of phase shift TD phase shift (PTDP) resulted in a 54% increase in data rate compared to the conventional design in the beam splitting case at IRS. The use of only two-bit phase shifters in the proposed PTDP is sufficient for near-optimal performance of the system's ability to focus the signal in the desired direction through the precoding technique, through which the losses caused by beam splitting can be compensated. As observed by comparing the proposed PTDP-based wideband precoding design with the conventional design, the results prove that the proposed design is capable of compensating for the array gain loss resulting from the double beam splitting effect occurring at both BS and IRS.